Influence of Critical Parameters on the Extraction of Concentrated C-PE from Thermotolerant Cyanobacteria (2024)
This work aimed to identify the influence of pH, molarity, w/v fraction, extraction time, agitation, and either a sodium (Na2HPO4 ·7H2O-NaH2PO4 ·H2O) or potassium buffer (K2HPO4 -KH2PO4 ) used in the extraction of C-phycoerythrin (C-PE) from a thermotolerant strain of Potamosiphon sp. An experimental design (Minimum Run Resolution V Factorial Design) and a Central Composite Design (CCD) were used. According to the statistical results of the first design, the K-PO4 buffer, pH, molarity, and w/v fraction are vital factors that enhance the extractability of C-PE. The construction of a CCD design of the experiments suggests that the potassium phosphate buffer at pH 5.8, longer extraction times (50 min), and minimal extraction speed (1000 rpm) are ideal for maximizing C-PE concentration, while purity is unaffected by the design conditions. This optimization improves extraction yields and maintains the desired bright purple color of the phycobiliprotein